The nature of the phenomenon of "mud eruption" in Ninh Thuan - Xuan, Pham Tich; Lien, Nguyen Thi; Dang, Pham Thanh; Pho, Nguyen Van; Tra, Doan Thu; Nga, Hoang Tuyet; Quynh, Bui Van (Vietnam Journal of Earth Sciences, 2016)
Detailed studies in mineral and chemical compositions of the muds at the mud mounds in the area of Loi Hai and Nhi Ha communes (Ninh Thuan province) indicated that muds are characterized by high clay contents (40-50%), which consists mainly montmorilonite (up to 36%). Exchangeable sodium percentage (ESP) of muds ranged from 15.61 to 68.73% and belong to the group of high sodicity. High concentration of montmorilonite makes mud in the mud mound able to swell significantly, on the other hand, the high sodicity leads to strong dispersal ability of the clay components, so they swelled easily when saturated with water inducing pressure pushing bulging, even making mud “spilled” onto the surface.ReferencesF.G. Bell and M.G. Culshaw, 2001: “Problem Soils: A Reviewfrom a British Perspective”. Proceeding of Problematic Soils Conference, Nottingham, 8 November 2001, 1-37. J.G. Davis, R.M. Waskom, and T.A. Bauder, 2014: Managing sodic soils. Colorado State University Extension. Fact Sheet 504, 3p. Nikos J. Warrence, Dr. James W. Bauder, and Krista E. Pearson, 2002: Basics of Salinity and Sodicity Effects on Soil Physical Properties. Department of Land Resources and Environmental Sciences, Montanta State University- Bozeman. Nguyễn Văn Phổ, 2013: Phong hóa nhiệt đới ẩm Việt Nam. Nxb. Khoa học Tự nhiên và Công nghệ. Hà Nội, 365tr. Đặng Xuân Phú, 2006: Đặc điểm địa hóa khoáng vật vỏ phong hóa các đá ở đới khô Thuận Hải. Luận án tiến sĩ, 120tr. Pichu Rengasamy, Sam North, Adrian Smith, 2010: Diagnosis and management of sodicity and salinity in soil and water in the Murray Irrigation region. The University of Adelaide, SA, 83p. Stephen Davies and Alison Lacey, 2009: Identifying dispersive soils. Farmnote. Department of Agriculture and Food. Note: 386. Stephen Davies and Alison Lacey, 2010: Managing dispersive soils. Farmnote. Department of Agriculture and Food. Note: 387. Phạm Văn Thanh, Trịnh Văn Nhân, 2004: Địa hóa môi trường đất đới khô và bán khô từ Nha Trang đến Bình Thuận. Tạp chí Địa chất, 282, tháng 5-6. Phạm Văn Thanh, Bùi Hữu Việt, Hồ Vương Bính, 2005:  Địa hóa môi trường đới khô và bán khô từ Nha Trang đến Bình Thuận. Địa chất và Khoáng sản, tập 9. Kỷ niệm 40 năm thành lập Viện nghiên cứu Địa chất và Khoáng sản (1965-2005), 403-409. http://www.terragis.bees.unsw.edu.au/terraGIS_soil/sp_exchangeable_ http://soils.cals.uidaho.edu/soil205-90/Lecture%2012/index.htm http://www.ccmaknowledgebase.vic.gov.au/brown_book/04_Sodic.